A Precoding Algorithm Based on Max-SNR in Massive MIMO System - Yuhua Wu (Dianxin kexue)
In order to obtain higher data transmission speed and greater array gain，a precoding algorithm based on max-SNR in massive MIMO system was proposed.The basic method of this algorithm was following.Firstly，the base station obtained MMSE channel estimation by received uplink pilot sequences，then the base station transmited downlink data to users after precoding.Terminal users derived the optimal precoding matrix by resolving a Rayleigh entropy optimization problem based on the received SNR.Simulation results show that the performance of the proposed algorithm is better than SVD algorithm，especially when the number of transmit antennas is large，the proposed algorithm is valuable in massive MIMO systems in the future.